The Effectiveness of Teams Games Tournament with Biodomino on Ecosystem Material to Enhance Studentâ€™s Activity and Learning Outcomes in SMAN 2 Salatiga - Faris, Ahmad; Pribadi, Tyas Agung; HB, F Putut Martin (FMIPA UNNES, 2018)
Ecosystem is considered as a notional topic due to lack of material visualization. An effective learning media is needed to help student in learning ecosystem. There are some factors that make some schools are unable to conduct an outdoor learning, that can be overcome through the model of Team Games Tournament (TGT) as a learning method with Biodomino as a supporting learning media. This study was aimed to determine the effectiveness of TGT with Biodomino on student activity and learning outcomes in ecosystem. The method used was quasi experiment with Nonequivalent Control Group Design. Result of this study showed that 100 percent of students participated in the experiment were in active category, with 81.25% of students got score of â‰¥77. It is concluded that learning the ecosystem unit by using TGT method with the help of Biodomino is an effective way to increase the student activity and learning outcomes.